The Ulcerative colitis - ustekinumab as a new biologic therapy, review 2024 - Felińska, Zuzanna; Silldorff, Julia; Fura, Tomasz; Dudek, Marcin; Zaucha, Radosław; Iszczuk, Oliwia; Anczyk, Stanisław; Gajkiewicz, Magdalena; Zając, Małgorzata (Quality in Sport, 2024)
Biologic agents have significantly transformed the therapeutic approach to ulcerative colitis. Anti-tumor necrosis factor (TNF) agents were the pioneering biologic drugs introduced to induce and maintain remission in this inflammatory bowel disease. Recently, ustekinumab, another biologic option, has been approved for the treatment of moderate-to-severe ulcerative colitis. Ustekinumab demonstrates a favorable clinical efficacy and safety profile for the treatment of moderately to severely active ulcerative colitis. As the first biologic agent to target the IL-12/IL-23 pathways, ustekinumab represents a viable therapeutic option, particularly following the failure of other biologics such as anti-tumor necrosis factor-α (TNF-α) antagonists and anti-α4ß7 integrin antagonists